Evaluasi Pengaruh Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Meningkatkan Keterampilan Non-Kognitif Siswa SMA Muhammadiyah 8 Ciputat - Diaz Arya Dimaskara; Mahmudin Sudin (CV Global Research Publication, 2026)
This study aims to evaluate the impact of the Project for Strengthening the Pancasila Student Profile (Proyek Penguatan Profil Pelajar Pancasila/P5) on improving non-cognitive skills among tenth-grade students at SMA Muhammadiyah 8 Ciputat. The research employed an evaluative method with a mixed-methods approach, combining quantitative and qualitative data. Quantitative data were collected through a non-cognitive skills questionnaire administered to 60 students before and after the implementation of P5, while qualitative data were obtained through observations and interviews with students and teacher facilitators. Quantitative analysis was conducted using a Paired Sample T-Test to examine differences in students’ non-cognitive skills, whereas qualitative data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of P5 has a significant and positive effect on students’ non-cognitive skills, particularly in the dimensions of collaboration (gotong royong), independence, and critical and creative thinking, as evidenced by increased Pretest and Posttest scores with significance values below 0.05. Qualitative findings further reveal positive changes in students’ learning attitudes and behaviors, including increased participation, responsibility, and teamwork in project-based learning activities. Therefore, this study concludes that P5 is an effective learning strategy for strengthening students’ non-cognitive skills and holistically fostering the Pancasila Student Profile within the implementation of the Merdeka Curriculum.